S5 Molecular Immunodiagnosis of TB Infection: A Pilot Study. (19th November 2012) - Connell, DW; Reuschl, A-K; Wenden, C; Witkowski, M; Kon, OM; Klenerman, P; Lalvani, A
Abstract : Introduction: Current interferon-gamma (IFN-γ) release assays (IGRAs) are not sufficiently sensitive to be used as a "rule-out" test for tuberculosis (TB). Antigen-specific gene expression of chemokines downstream of, and amplified by, IFN-γ might demonstrate such sensitivity, and can be performed with very small volumes of blood. 1 Here we assess the performance and sensitivity of two IFN-γ-dependent gene expression platforms in the peripheral blood mononuclear cells of individuals with and without TB. Methods: 23 individuals with active TB, 12 individuals with latent TB infection (LTBI), and 18 controls had simultaneous IFN-γ ELISpot assays and qRTPCR of CXCL-9 and CXCL-10, following stimulation with the immunodominant antigens ESAT-6, CFP-10 and EspC (6 gene expression assays in total). Test performances of the 6 gene expression assays were compared to the ELISpot. Results: Gene expression of CXCL-9 and CXCL-10 was antigen specific, correlating well with each other and with the IFN-γ ELISpot (Spearman Rank Correlations ranging from r=0.648 to 0.74). Gene expression of either was not significantly different between those with active TB and LTBI. Receiver-operating characteristic curves indicated good test performances for all the gene expression assays (AUC ranging from 0.918 to 0.959) and agreements between the ELISpot and gene expression platforms was good (κ statistic ranging from 0.403–0.496). After constructing cut-offs for sensitivity for individual antigens, with cut-offs for specificity matching or exceeding that of the IFN-γ ELISpot, the sensitivity of TB diagnosis with gene expression was superior to ELISpot in 5 out of the 6 assays, although these differences were not statistically significant. Sensitivity was equivalent when antigens were combined, as in the commercially available T-Spot ® . TB. Conclusions: These pilot data indicate that gene expression of IFN-γ-dependent cytokines is a robust, sensitive and specific method of TB diagnosis, and carries potential to be a more sensitive platform that the current gold standard – IFN-γ ELISpot. Larger studies with appropriate power are now required in similar populations to investigate this approach definitively. References: Kasprowicz VO, Mitchell JE, Chetty S, Govender P et al. A molecular assay for sensitive detection of pathogen-specific T-cells. PLoS One. 2011; 6(8):e20606. Epub 2011 Aug 11.